Conservation Management Model of Subayang River in the Kampar Regency, Province of Riau based on Local Wisdom using Belida Fish (Chitala sp.) as Bioindicator - Ahmad, Darmadi; Sukendi, Sukendi; Saam, Zulfan; Suwondo, (Ecological Questions, 2023)
This research was conducted on the Subayang River in Kampar Regency, Riau Province, Indonesia, from January to December 2019. This research aims to determine the physical and chemical water characteristics of the Subayang River and the trend of the Belida fish (Chitalla sp.) population for constructing a river conservation management model based on local wisdom. To investigate the water's physical characteristics, a water sample was acquired from the Subayang river on three stations (upstream, middle stream, and downstream). The water sample was collected on each station iteratively at three different points at the river stream's left, middle, and right sides. The trend of Belida fish population data was gathered from interviews with the fishermen. Moreover, interviews with the traditional figure of the society around the Subayang river were also conducted. Then, the conservation model of the Subayang river was constructed by analyzing the interview and the population of Belida fish results using a system dynamic model. The investigation of the water’s physical and chemical properties shows that the Subayang river has a suitable environment for the growth of Belida fish. However, the Belida fish population trend in the last four years tends to decrease. The existence of "lubuk larangan" and "pantang larang adat", are local wisdom that gives a positive affection towards the Belida fish population. Those traditional rules can restrict citizens from doing illegal fishing which hardly affects the Belida fish population.